Isolation Of Compounds Of Steroids Teripang Gamat (Stichopus variegatus) With Various Types Of Solvents - Meydia Meydia; Ruddy Suwandi; Pipih Suptijah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
AbstractSea cucumber is one of the fisheries commodity that has an important economic value. Generally is traded in dried form (beche-de-mer). One of thebioactive substances contained in sea cucumber is steroid compounds that serves as an aphrodisiac and sex reversal. The purpose of this study was to extract the steroid of the gamma sea cucumber by using three types of solvents (methanol, ethyl acetate and hexane) and get the best solvent in producing the highest yield of the steroids. The study revealed that steroid of gamma sea cucumber (Stichopus variegatus) dissolved completely ethyl acetate (semi-polar solvent) during the first phase, second phase and the third phase of extraction. In the methanol (polar solvent) steroids only dissolved in the first extraction phase, while using the hexane (non polar solvent) steroid was undetectable. Fractionation by thin layer chromatography was obtained two fractions that identified as cholesterol (Rf = 0.96) and testosterone (Rf = 0.91).